Purified polysaccharides extracted from grey oyster mushroom [Pleurotus sajor-caju (Fr.) Sing.] stimulate glucose uptake in c2c12 myotubes through the activation of AMP-activated protein kinase (AMPK) and glucose transporter 1 (GLUT1) proteins - Kulwanit Patninan,; Decha Sermwittayawong,; Supada Nuinamwong,; Wipapan Khimmaktong,; Kusumarn Noipha,; Nongporn Hutadilok-Towatana, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The grey oyster mushroom [Pleurotus sajor-caju (Fr.) Sing.], an edible mushroom, has been known as a source of bioactive compounds, including polysaccharides. Polysaccharides from this mushroom have been shown to possess antidiabetic activity both in vivo and in vitro. However, antidiabetic mechanism of partially purified or purified polysaccharides from the gray oyster mushroom has not been characterized. In this study, we extracted and purified polysaccharides from gray oyster mushrooms and used them to investigate the antidiabetic mechanism in the context of C2C12 myotubes. Using Fourier Transform Infrared spectroscopy (FTIR) analysis and enzymatic assay, we showed that the polysaccharide sample, namely 9S1-1, contains β-glucose, α-glucose, and mannose as the monosaccharide composition, and β-glucan is the major type of polysaccharide in the sample. This 9S1-1 sample dosedependently stimulated glucose uptake in C2C12 myotubes. Further analysis showed that the sample activated the AMP-activated protein kinase (AMPK) but not Akt serine/threonine kinase (AKT) phosphorylation, suggesting that the stimulation is AMPK-dependent. Moreover, we showed that compound c, an inhibitor of AMPK, inhibited glucose uptake in 9S1-1-stimulated cells, confirming the requirement of AMPK in the glucose uptake activated by the 9S1- 1 sample. In addition, it promoted glucose transporter protein type 1 (GLUT1) but not GLUT4 protein expression. These results suggest that GLUT1 may be responsible for the stimulation of glucose uptake in 9S1-1-activated cells. Together, these data illustrate the antidiabetic mechanism of polysaccharides isolated from the gray oyster mushroom and the potential use of the polysaccharide as an antidiabetic agent.